Introducing the concepts of measurement accuracy and precision in the classroom - Perea Martins, J. E.M. [UNESP] (IOP Publishing, 2019)
This work proposes simple experiments to introduce some fundamental concepts of the measurement area. It associates theory and practice through a strategy where the students create a real temperature data set with an Arduino board and three LM35DZ sensors and later use mathematical software to identify theoretical concepts as measurement accuracy and precision.